IDENTIFICATION OF THE kdr MUTATIONS IN VGSC GENE OF THE DENGUE MOSQUITOES AEDES ALBOPICTUS COLLECTED FROM HANOI AND HAIPHONG - Kim Lien, Nguyen Thi; Hien, Nguyen Thu; Hoang, Nguyen Huy; Hong Ngoc, Nguyen Thi; Huong Binh, Nguyen Thi (Vietnam Journal of Biotechnology, 2018)
Vietnam is one of the countries that is affected by dengue fever in Southeast Asia. The dengue epidemic is becoming increasingly more complex so it is necessary to have a well control to vectors in order to limit the spread of the disease. The Aedes albopictus mosquito is determined as one of the two major vectors that transmitted the dengue. Recent research shows that A. albopictus is present in some parts of Hanoi and Haiphong. In order to control the vector as well as the disease, it is necessary to understand the level of resistance and the resistance mechanism of the vector. Two important resistance mechanisms of insect were known as the mutations in the target protein of the insecticides and enhancing the activity of enzymes that participate in the resolution of the insecticides. In this study, the mosquito samples were collected from Hanoi and Haiphong to identify the level of resistance and detect the knock down resistance mutations in voltage gated sodium channel (VGSC) in membrane of nervecell of mosquito. The results of insecticide susceptibility test showed that A. albopictus in Hanoi and Haiphong were still sensitive to organophosphate but resistant to DDT, carbamate and pyrethroid. Ser989Pro, Ile1011Met, Val1016Gly and Phe1534Cys mutations were not deteced in A. albopictus in Hanoi and Haiphong. However, we detected a novel mutation Tyr986His in VGSC protein.